Critical Success Factors for Implementing Total Quality Management in the Libyan Public Health Sector - سعد عبدالسلام; الفيتوري أشرف (Dirasat in Economics and Business, 2017)
The purpose of this paper is to investigate total quality management (TQM) implementation in the Libyan Public Health Sector (LPHS), in order to assist Libyan public health sector to effectively implement their TQM initiatives. Using existing measures in the literature, five factors have been identified as being critical for successful TQM in the Libyan public health sector, namely; top management support, education and training, patients focus and satisfaction, supplier management, continuous improvement culture. The data used in this study were obtained using a survey questionnaire by (64) managers in the Libyan Public Health Sector. The results revealed that the LPHS is at a low level for TQM implementation and does not make sufficient efforts to improve its quality. This paper contributes to the existing knowledge by investigating the five critical success factors implementation of TQM in a different context. Results from this paper will help any future efforts to develop a framework for implementing TQM in Libyan public health sector in the future.